Features of cast iron welding with electrodes with oxidizing сoating - Elfimov, V.; Єлфімов, В. В. (Харківський національний автомобільно-дорожній універститет, 2024)
Application issues of manual arc cold-welding of cast iron by electrodes on Cv-08A wire with oxidizing coating containing oxidizing agents, slag-forming and stabilizing elements of marble, hematite, quartz sand, chromium oxide, aluminum powder, mica and soda are considered.
Особливості зварювання чавуну електродами з окислювальним покриттям
Keywords: cast iron; welding; oxidizing agents; hematite; coating; чавун; зварювання; окислювачі; гематит; покриття; 621.791.01